Integrating Blended Learning in Intensive English Course in Higher Education: A Theoretical and Practical Perspective - Fifi Nur Ulwiyah (CV. Edutechnium Indonesia, 2025)
This article explores the implementation of blended learning in the Intensive English Course in Higher Education. The integration of online learning through English Discoveries (ED) with offline classroom sessions aims to improve students' English proficiency by offering flexible, interactive, and learner-centered experiences. The paper is grounded in constructivist and social learning theories, offering both a theoretical foundation and practical analysis of this pedagogical approach. The study employed a qualitative descriptive method to investigate student and lecturer perspectives. Data were collected through semi-structured interviews with five English instructors and ten students, classroom observations, and document analysis of course syllabi and student task records. The findings suggest that blended learning fosters greater learner autonomy, digital literacy, and language competence. Students reported increased motivation due to the accessibility and interactivity of ED, while instructors emphasized that face-to-face interaction remained vital for developing speaking skills and addressing comprehension difficulties. However, challenges such as time management difficulties, inconsistent motivation, and technological barriers (particularly unstable internet access) were also identified. The study concludes that successful blended learning implementation requires adequate institutional support, technological infrastructure, and continuous professional development for instructors.